Response to 'Systematic reviews do not always capture context of real-world intervention programmes for childhood obesity' by Wild et al., 2021 in BMC Public Health - Robyn Littlewood; Oliver J. Canfell; Jacqueline L. Walker (BMC, 2021)
Abstract In a correspondence to BMC Public Health, Wild et al. respond to our systematic review that synthesised results of interventions to prevent or treat childhood obesity in Māori and Pacific Islanders. Our review included the Whānau Pakari study as one of six included studies - a multidisciplinary intervention for Māori children and adolescents living with obesity led by their research team. Our review suggested that future research can incorporate stronger co-design principles when designing culturally-tailored interventions to maximise cultural specificity, enhance engagement, facilitate program ownership and contribute to improved health and weight-related outcomes. We commend Whānau Pakari and the team of Wild et al. on their sustained commitment to addressing obesity in priority populations and agree that systematic reviews struggle to capture real-world context of interventions for complex diseases such as obesity. In this article, we respond sequentially to the comments made by Wild et al. and (1) clarify the scope of our review article (2) reiterate our commendation of mixed-methods approaches that capture real-world context (3) explain a referencing error that caused a misinterpretation of our results (4) clarify our interpretation of some Whānau Pakari characteristics (5) welcome partnership to facilitate shared learning with Wild et al.